(untitled) (Heritage, 2021)
The basic concept of this paper is derived from the view that the openness and complex structure of the literary text provide an opportunity for achieving interdisciplinary integration. However, the implementation of interdisciplinary integration requires good planning. For this reason, the paper presents an innovative model for planning an integrative approach in Serbian language teaching. Specifically, it depicts micro-planning for the integrative approach to the children’s book Bosonogi i nebo (A Barefoot Boy and the Sky) by Branislav Crnčević in the fourth grade of primary school that allows the Serbian Language and Literature course to be integrated with the following courses within a single school period: Math, Science & Social Studies, Civic Education, Art Education and Music Education. The presented micro-plan encompasses concretized outcomes of all previously mentioned courses, as well as planned activities that contribute to their implementation. Given that the integrative approach is insufficiently represented in teaching practice, one of the basic implications of this paper is to highlight the need for implementation and evaluation of this (and similar) models in teaching practice.